Decolonizing global health research: experiences from the women in health and their economic, equity and livelihood statuses during emergency preparedness and response (WHEELER) study - Adam, Ahmed; Lazarus, Lisa; Kina, Bernadette; Lorway, Robert; Mazoya, Bilali; Mantel, Michaela; Temmerman, Marleen; Avery, Lisa; Langat, Evaline (Frontiers in Public Health, 2025)
Decolonizing global health research involves rethinking power structures and research collaboration to prioritize the voices and experiences of communities that have been historically marginalized. Cross-sectoral and cross-regional partnerships based on reciprocity, trust, and transparency can be facilitated by decolonized research frameworks. To address global health issues in a way that is inclusive, context-specific, and genuinely advantageous to all parties involved, especially communities most impacted by health disparities, the ethics behind this change is imperative. We applied a decolonizing health research approach to the Women in Health and their Economic, Equity, and Livelihood Statuses During Emergency Preparedness and Response (WHEELER) study to explore the connections between gender, health, and economic equity in times of crisis in two counties in Kenya. This paper outlines seven key dimensions that guided the WHEELER study in transforming power dynamics in research, decolonizing research processes, and fostering equitable partnerships. The study employed participatory methodologies, integrating the Equity in Partnership instrument from the Canadian Coalition for Global Health Research (CCGHR) Principles, human-centered design (HCD), and gender-based analysis to ensure inclusivity, gender sensitivity, and active participation. The participatory approach was implemented through the engagement of a Community Research Advisory Group (CRAG) and a Local Advisory Board (LAB). Utilizing mixed methods and community-engaged processes, the study fostered reciprocal growth, learning, and change among local health officials and research teams. Our participatory approach fostered strengthened engagement, promoted shared decision-making, and enhanced the sense of ownership among policy implementers throughout the research process.